Efektivitas Metode Karyawisata terhadap Peningkatan Keterampilan Menulis Bahasa Arab Siswa - Thoyibah, Naim Hikmatut; Maulana, Asep; Anam, Syamsul; Habibah, Nur Faiz (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
This study aims to analyze the effectiveness of the Field Trip Method (Karyawisata) in improving students’ writing skills (Maharah Kitabah) in Arabic language learning at MTs Silahul Muslimin Banyuwangi. The background of this research is the need for more engaging and interactive learning strategies compared to traditional classroom methods. This study employs a qualitative descriptive approach conducted in May 2025, involving Arabic language teachers, school administrators, and students. Data were collected through observation, interviews, and documentation, and analyzed through three stages: data reduction, data presentation, and data verification. The results show that the implementation of the Field Trip Method enhances students’ motivation, creativity, and writing ability through enjoyable and contextual learning experiences. Therefore, the Field Trip Method is proven to be an effective and innovative pedagogical approach that strengthens students’ Arabic writing skills at the junior secondary school level.